Milk Osteopontin Promotes Intestinal Development in Early Life by Increasing Expression of Osteopontin Receptors. (29th May 2020) - Jiang, Rulan; Lo, Jamie; Prell, Christine; Lönnerdal, Bo
Abstract: Objectives: Osteopontin (OPN), a phosphorylated glycoprotein, is abundantly present in both human and mouse milk, making the mouse a good model to study functions of milk OPN. OPN is a pleiotropic protein involved in many biological processes such as cell proliferation and differentiation. OPN initiates signaling pathways to exert its multiple functions by binding to its receptors on the surface of target cells. Since milk OPN is partly resistant to in vitro digestion, the current study aimed to investigate roles of milk OPN on intestinal development in early life. Methods: A mouse model established by our group was used. In this model, wild-type (WT) mouse pups were either nursed by WT or OPN knock-out (KO) dams, receiving milk with or without OPN from postnatal days 0 to 21 (P0−P21). Whether milk OPN is resistant to in vivo digestion and effects of milk OPN on intestinal development were examined. Results: Milk OPN was resistant to in vivo digestion as indicated by immunoblotting using intestinal contents from P12 pups. Young pups (P4 and P6) nursed by WT dams (OPN + group) exhibited significantly longer small intestines than did pups nursed by OPN KO dams (OPN- group), but older pups had similar lengths in both groups (P8 to P30). Further, OPN + pups had a larger inner surface than did OPN- pups at P10 and P20 as revealed by histological analysis of the ratio of villus height/crypt depth. The activity of an intestinal differentiation marker (alkaline phosphatase) was significantly higher in the OPN + group than the OPN- group at P30. In addition, compared with the OPN- group, the OPN + pups (P30) had better differentiation based on the observation that more goblet cells and Paneth cells appeared in the small intestine.. To determine how milk OPN exerts its functions on the intestine, effects of milk OPN on expression of OPN receptors were then determined. qRT-PCR results showed that milk OPN increased transcription of OPN receptors, including integrin αv, integrin β3, and CD44 in duodenum and jejunum from P4 to P30 mouse pups. Immunoblotting results also indicated that milk OPN increased the protein levels of integrin αv . Conclusions: Milk OPN promotes intestinal proliferation and differentiation by up-regulating expression of OPN receptors in early life. Funding Sources: This study was in part funded by Mead Johnson Nutrition.